Industrial Applications of Microalgal Biotechnology: A Novel Approach to Disease Mitigation - Ukolobi, Odiri; Chukuka, Vivian Ishioma; Onianwah, Ifeanyichukwu Fidelis; Adeola, Morenike Omotayo; Onoriasakpobare, Felix Omamuyovwe (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
A new sustainable method of disease prevention is offered by microalgal biotechnology, which takes advantage of microalgae's special qualities as "cellular factories." A wide range of bioactive substances with medicinal qualities can be produced by cultivating these small photosynthetic organisms. The prevalence of chronic diseases and the emergence of drug-resistant bacteria are two health issues that this industrial application promises to address. The creation of novel antimicrobial agents such as antibiotics, antivirals, and antifungals is one of the main uses. These medicines are desperately needed to fight drug resistance. Additionally, microalgae can be genetically modified to generate monoclonal antibodies and subunit vaccinations, providing a secure and affordable substitute for conventional techniques. They are also a great source of antioxidants and anti-inflammatory substances including polyunsaturated fatty acids (PUFAs) and carotenoids, which are essential for controlling and avoiding chronic illnesses. In addition to direct therapies, microalgal cells can be utilized as sophisticated drug delivery systems, as well as sources of functional foods and nutraceuticals that improve general health. By eliminating contaminants, their function in bioremediation reduces the spread of antibiotic resistance and enhances environmental health. This analysis emphasizes the diverse potential of microalgal biotechnology as a cutting-edge and significant approach to the prevention of disease worldwide.